Withania somnifera aqueous extract facilitates the expression and release of GnRH: In vitro and in vivo study. (October 2015) - Kataria, Hardeep; Gupta, Muskan; Lakhman, Sukhwinder; Kaur, Gurcharan
Abstract: Ashwagandha ( Withania somnifera ) has a long history in traditional medicines as an aphrodisiac. It has been known to influence sexual behaviour in animal models but mechanism of action is still unknown. The present study was aimed to investigate the mechanisms by which Ashwagandha extract exert its gonadotropic activities. Due to the complexity of neuroendocrine pathways, there are limited in vitro models available despite the strong demand for such systems to study and predict neuroendocrine effects of chemicals or natural products. Immortalized rat hypothalamic GnV-3 cell line was investigated as a model to screen for neuroendocrine effects of Ashwagandha extract. GnV-3 cells were cultured under different media conditions and evaluated after treatment with Ashwagandha water extract, for GnRH expression and release by immunostaining and ELISA respectively. These cells acquired differentiated morphology, characteristic shape displayed by preoptic GnRH neurons in vivo . In addition, GnV-3 cells exhibited upregulation of plasticity related polysialylated neural cell adhesion molecule (PSA-NCAM) and mature dendrite marker microtubule associated protein (MAP2) as well as GnRH expression and release. Chloroform fraction of the extract proved to exhibit all the bioactive properties as it induced differentiation and upregulated GnRH and MAP2 expression in GnV-3 cells, similar to Ashwagandha extract. Withanone and Withaferin A were found to be present in ASH-WEX and chloroform fraction while Withanone came out to be the major constituent of chloroform fraction. The preliminary in vivo studies in adult male animals showed that ASH-WEX was able to upregulate the GnRH levels although non-significantly. Taken together, this data demonstrate significant morphological and physiological changes in GnV-3 cells after treatment with Ashwagandha extract and may suggest the potential beneficial effects of Ashwagandha on reproductive functions in vivo . Graphical abstract: Highlights: Gonadotropic activities of Ashwagandha at cellular levels were investigated. Ashwagandha lead to upregulation of GnRH expression and release. Morphological changes were concomitant with upregulation of PSA-NCAM and MAP-2. Withanone and withaferin A are present ASH-WEX.